(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
The combination of the rhetoric and poetry formed a prominent phenomenon at the dissenter poets in the Umayyad era, so their effects showed in their poetry which was characterized with a clear rhetoric. One of the most prominent dissenter poets is Qatari Bn Al-Fojaa; imam Al-Azarika and their orator and poet whose poetry come enveloped with evidences and the methods of convincing between explanation and detailing to improvement and disfigurement. Everything is intervened by Koranic quotes which help to stabilize the cogency and the strengthening of its persuasion. Qatari tend to use the method of the scenic Moqabala whether on the level of the single verse or on the level of the whole poem. This helps to return the imaginative side to his poetry and the lessening of the domination of the rhetorical tendency on it, as well as what this style achieves in marking time between the poetic meanings and rhetorical meanings to get the self-comfort which guarantees the perfection of the respond.